STUDI FENOMENOLOGI: PENGALAMAN PSIKOLOGIS WANITA PASCAHISTEREKTOMI - Sofian, Ridwan; M. Nur, Mangsur (Jurnal Pendidikan Kesehatan (e-Journal), 2024)
Post-hysterectomy women tend to experience psychological problems that impact their mental health. This study aims to explore the psychological experiences of post-hysterectomy women using a qualitative method with a phenomenological approach. Participants were selected through purposive sampling method with inclusion criteria: (1) Have undergone hysterectomy, (2) Women aged 15-64 years. The research was conducted for 22 days at Wava Husada Kepanjen Hospital with semi-structured interviews. Data were obtained through interviews with 6 post-hysterectomy participants. Analysis used the Interpretative Phenomenological Analysis technique. Eleven themes emerged: (1) Tumor growth as the cause of hysterectomy, (2) No longer having a uterus, (3) Unable to menstruate and conceive again, (4) Loss of femininity, (5) Fear of abandonment by spouse, (6) Feeling powerless in the situation, (7) Resigned acceptance of everything that happens, (8) Withdrawing from the outside environment at the onset of surgery, (9) Decreased sexual behavior, (10) Spouse as strength to forget problems, (11) Hope for always being healthy and happy. Participants understand that hysterectomy means no longer having a uterus, unable to menstruate and conceive again. This understanding leads to negative thoughts, perceiving themselves as lacking in femininity, and experiencing negative feelings of powerlessness and behaviors related to decreased sexual behavior.